Búho real – Bubo bubo (Linnaeus, 1758) ... - Penteriani, Vincenzo; Delgado, María Del Mar; Salvador Milla, Alfredo (Salvador Milla, Alfredo, 2016)
Aves - Orden Strigiformes - Familia Strigidae en la Enciclopedia Virtual de Vertebrados Españoles, http://www.vertebradosibericos.org/. Versiones anteriores: 30-03-2010 ... : A comprehensive review of the natural history of the Eurasian Eagle Owl Bubo bubo in Spain. ...